Проблемы динамического межотраслевого планирования - Маевский Владимир Иванович (Наука, 1974)
Экземпляры: КХ (20240311) / Инвентарный номер: 582199 / Сис.шифр: 33С / Авт.знак: М 13 / ГРНТИ: 06 / ББК: 65